Pelvic Mass 21 Years after Total Hip Arthroplasty. (18th June 2013) - Miller, Joe; Tarter, Thomas H.
Abstract : Background . Long-term urologic complications after total hip arthroplasty are rare, and reports in the urologic literature are scant. We present a recent case and review the relevant literature. Case . A 77-year-old man was referred to the urology clinic for a single episode of gross painless hematuria, abnormal urine cytology, and pelvic mass. He had a significant smoking history. Surgical history included right total hip arthroplasty 21 years prior. Results . Pelvic ultrasound revealed a large mass abutting the right bladder wall. Subsequent computed tomography indicated that the mass was extrinsic to the bladder. Results of computed tomography-guided biopsy of the mass were consistent with foreign body granuloma. Surveillance imaging confirmed no growth or progression, and intervention was deferred. Conclusion . Long-term complications of total hip arthroplasty may present with signs and symptoms of urologic disease. Reports in the urologic literature are rare.